Intelectualidad y política: el convictorio de San Carlos y Bartolomé Herrera - Gálvez Montero, José Francisco (2020)
Intellectuality and politics have been recurrent elements in the management of power, directly or indirectly. The article highlights the influence of the Convictorio de San Carlos (Lima) in strengthening the prevailing regime. From him, we show José Faustino Sánchez Carrión, liberal revolutionary, and Bartolomé Herrera, conservative liberal, each of whom in his time and context had the leadership in politics. A fact that highlights the importance of the contributions of the Study Centers in the management of the country.